ANALISIS FAKTOR-FAKTOR FUNDAMENTAL YANG MEMPENGARUHI RETURN SAHAM PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ 45 DI BURSA EFEK INDONESIA PERIODE TAHUN 2013 â 2015 - Ika, Desi; Listiorini, Listiorini (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
The capital market is a means to obtain funds from the public to be transferred to various business sectors in order to carry out the investment. In general, investors will be willing to invest in the capital market because there is a feeling of security in investment. Investing in the capital market, analysts and investors can make investment approaches that can be broadly divided into two approaches, technical analysis and fundamental analysis. The purpose of this study was to investigate the influence of fundamental factors : Price Earning Ratio (PER), Debt to Equity Ratio (DER), Return on Equity (ROE), and Price to Book Value (PBV) on stock returns of companies listed in the LQ 45 at the Indonesia Stock Exchange. The population consisted of 45 companies in the LQ 45 period from 2013 to 2015 and obtained 28 samples using purposive sampling technique. Based on the results of this study concluded that simultaneous Price Earning Ratio (PER), Debt to Equity Ratio (DER), Return on Equity (ROE), and Price to Bo Value (PBV) effect on stock returns of companies listed in the LQ 45 at Indonesia stock exchange. Partially, variable Price Earning Ratio (PER) and Debt to Equity Ratio (DER) significantly affects stock returns. While variable Return On Equity (ROE) and Price to Book Value (PBV) had no significant effect on stock returns.Keywords: stocks, ROE, DER, PER, PBV